Characterizing risk factors for pediatric lamp oil product exposures. (November 2013) - Sheikh, S.; Chang, A.; Kieszak, S.; Law, R.; Bennett, H. K. W.; Ernst, E.; Bond, G. R.; Spiller, H. A.; Schurz-Rogers, H.; Chu, A.; Bronstein, A. C.; Schier, J. G.
Abstract Poisonings from lamp oil ingestion continue to occur worldwide among the pediatric population despite preventive measures such as restricted sale of colored and scented lamp oils. This suggests that optimal prevention practices for unintentional pediatric exposures to lamp oil have yet to be identified and/or properly implemented. Objective. To characterize demographic, health data, and potential risk factors associated with reported exposures to lamp oil by callers to poison centers (PCs) in the US and discuss their public health implications. Study design. This was a two part study in which the first part included characterizing all exposures to a lamp oil product reported to the National Poison Data System (NPDS) with regard to demographics, exposure, health, and outcome data from 1/1/2000 to 12/31/2010. Regional penetrance was calculated using NPDS data by grouping states into four regions and dividing the number of exposure calls by pediatric population per region (from the 2000 US census). Temporal analyses were performed on NPDS data by comparing number of exposures by season and around the July 4th holiday. Poisson regression was used to model the count of exposures for these analyses. In the second part of this project, in order to identify risk factors we conducted a telephone-based survey to the parents of children from five PCs in five different states. The 10 most recent lamp oil product exposure calls for each poison center were systematically selected for inclusion. Calls in which a parent or guardian witnessed a pediatric lamp oil product ingestion were eligible for inclusion. Data on demographics, exposure information, behavioral traits, and health were collected. A descriptive analysis was performed and Fisher's exact test was used to evaluate associations between variables. All analyses were conducted using SAS v9.3. Results. Among NPDS data, 2 years was the most common patient age reported and states in the Midwestern region had the highest numbers of exposure calls compared to other regions. Exposure calls differed by season (p < 0.0001) and were higher around the July 4th holiday compared to the rest of the days in July (2.09 vs. 1.89 calls/day, p < 0.002). Most exposures occurred inside a house, were managed on-site and also had a "no effect" medical outcome. Of the 50 PC-administered surveys to parents or guardians, 39 (78%) met inclusion criteria for analysis. The majority of ingestions occurred in children that were 2 years of age, that were not alone, involved tiki torch fuel products located on a table or shelf, and occurred inside the home. The amount of lamp oil ingested did not appear to be associated with either the smell (p = 0.19) or the color of the oil (p = 1.00) in this small sample. Approximately half were asymptomatic (n = 18; 46%), and of those that reported symptoms, cough was the most common (n = 20, 95%) complaint. Conclusions. Lamp oil product exposures are most common among young children (around 2 years of age) while at home, not alone and likely as a result of the product being in a child-accessible location. Increasing parental awareness about potential health risks to children from these products and teaching safe storage and handling practices may help prevent both exposures and associated illness. These activities may be of greater benefit in Midwestern states and during summer months (including the period around the July 4th holiday).